Mg–Mg-bonded compounds with N, N′-dipp-substituted phenanthrene-diamido and o-phenylene-diamino ligands. Issue 7 (25th January 2019) - Ma, Meimei; Wang, Huanhuan; Wang, Juju; Shen, Lingyi; Zhao, Yanxia; Xu, Wen-Hua; Wu, Biao; Yang, Xiao-Juan
Abstract : Two Mg–Mg-bonded compounds were synthesized by using phenanthrene-diimine and o -phenylenediamine ligands; their UV-Vis and fluorescence spectra and reactivity were studied. Abstract : Two Mg–Mg-bonded compounds were synthesized by using the ligands N, N ′-bis(dipp)-phenanthrene-9, 10-diimine (L 2 ) and N, N ′-bis(dipp)- o -phenylenediamine (H2 L 3 ; dipp = 2, 6-diisopropylphenyl). These new Mg(i ) species were characterized by X-ray diffraction, NMR, UV-Vis and fluorescence spectroscopy, and DFT computations. Their reactions with unsaturated organic molecules were examined.